The Factors That Affect The Satisfaction of Local Coffee Shop Customers in The 4.0 Industry Era - Nanda Rusti; Irham Irham; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Customer satisfaction is the opinion of consumers, in the form of the performance of a product or service that meets their expectations. Generally, successful businesses highly care about customer satisfaction as profit. Therefore, this study aims to analyze the effects of: (1) perceived quality, (2) price, (3) industrial application 4.0, and (4) products innovation on customer satisfaction in the local coffee shop business in the Special Region of Yogyakarta. The data were collected using online questionnaires sent through direct message on instagram account of each customer who posted a photo with a tag or a hashtag from one of the 31 local coffee shops whilst they were enjoying a cup of coffee drink. All customers had the same opportunity to be sampled according to a representative proportion at each local coffee shop. The determination of the minimum sample used was 165 respondents. The samples analyzed were 173 respondents collected from 450 questionnaires completed by customers in which only 176 questionnaires were returned, and three questionnaires happened to be outliers that needed to be eliminated. The data were analyzed using the Structural Equation Modeling (SEM) provided in the AMOS application. The results indicated that customer satisfaction was positively influenced by perceived quality, industry 4.0 implementation, and products innovation, while price negatively affected customer satisfaction. It is highly recommended to maintain and improve perceived quality, industry 4.0 implementation, products innovation, and consider in determining extremely crucial prices for the local coffee shops to acquire customer satisfaction.